(untitled) (MAUSAM, 2016)
Location specific and integrated farming system based technological management options reduce the climatic risk and better utilization of available natural resources produce higher agricultural productivity and thereby enhance food and livelihood security of small and marginal farmers of India. The significance of IFS approach is supportive in enhancing productivity to meet the food, feed and fuel for ever increasing human and animal population. It also increases the land productivity, profitability and also generate employment. Since small farms are often vulnerable to natural vagaries like flood, drought and farming remains at risk. Due to industrialization and population growth, the horizontal expansion of agricultural area is not possible. The vertical expansion in small farms is possible by integrating appropriate farming system components requiring less space and time and ensuring periodic income to the farmers. A farming system model was synthesized based on the studies conducted at ICAR-IIFSR located in western plain zone of Uttar Pradesh for a period of six years (2004-2010) revealed that Integrated farming system approach applied on a piece of 1.5 hectare irrigated land, besides fulfilling all the requirement of 7 members household food and fodder demand (animals) inclusive cost of production, could create an additional average annual savings of Rs. 47000/- in four fours of its establishment and more than Rs. 50000/- in subsequent years. the family gets some income round the year and another benefit is if due to any extreme event occurred at any time of the year, the farmer will get some income from any of the enterprises, so that it will cater to the need of the food security. Since each enterprise react differently to extreme weather events; the influence of droughts/floods/ higher temperature will be different to different enterprises and because of the diversification, the farmer will get some income from their enterprises, so that he can sustain under difficult times. This manuscript analyses how farming system approach is different and site specific and also how it will decrease the vulnerability under extreme climatic situations with some examples.